2016
DOI: 10.1152/ajpheart.00728.2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of segmented vessel size due to limited imaging resolution on coronary hyperemic flow prediction from arterial crown volume

Abstract: van Horssen P, van Lier MG, van den Wijngaard JP, VanBavel E, Hoefer IE, Spaan JA, Siebes M. Influence of segmented vessel size due to limited imaging resolution on coronary hyperemic flow prediction from arterial crown volume. Am J Physiol Heart Circ Physiol 310: H839 -H846, 2016. First published January 29, 2016 doi:10.1152/ajpheart.00728.2015.-Computational predictions of the functional stenosis severity from coronary imaging data use an allometric scaling law to derive hyperemic blood flow (Q) from corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The variability in the total number of vessels for a given segmented network highlights the variation attributed to segmentation. This would be expected in other networks that exhibit dispersive branching patterns, such as the coronary arteries (10) or cerebral vasculature (31). We employed a generation based ordering scheme to describe the branching structure, where each bifurcation is considered a new generation of blood vessels.…”
Section: Segmentation and Construction Of Network Graphsmentioning
confidence: 99%
See 3 more Smart Citations
“…The variability in the total number of vessels for a given segmented network highlights the variation attributed to segmentation. This would be expected in other networks that exhibit dispersive branching patterns, such as the coronary arteries (10) or cerebral vasculature (31). We employed a generation based ordering scheme to describe the branching structure, where each bifurcation is considered a new generation of blood vessels.…”
Section: Segmentation and Construction Of Network Graphsmentioning
confidence: 99%
“…However, inherent uncertainty is present as most image segmentation software require manual specification of the image intensity thresholds (pre-segmentation parameters) between background and foreground. For example, van Horssen et al [10] showed that variation in image resolution affected the cumulative volume of a cast of the coronary arterial tree after segmentation. Rempfler et al [11] compared segmentation algorithms on retinal images, showing that posterior probability estimates for foreground pixels varied with different segmentation techniques when compared with the true segmentation or so-called ground truth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, much remains to be understood regarding the causal relationship between coronary microvascular disease and ischemic heart disease. New methods for high‐resolution ex vivo imaging and morphometry of the entire coronary vasculature in pigs, other large mammals,and mice will help fill these gaps. However, technological advances, such as biosensors for understanding intracellular and macro‐scale signaling and mechanics; higher resolution and speed, imaging technologies that can penetrate into deeper layers of tissues in vivo, including intrinsic fluorescence; fate mapping for disease etiology, eg, site for angiogenesis; and new transgenic and conditional animal models are needed to further advance the field.…”
Section: Vascular Dynamicsmentioning
confidence: 99%